If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -2) = -8(x + 4) Reorder the terms: 6(-2 + 2x) = -8(x + 4) (-2 * 6 + 2x * 6) = -8(x + 4) (-12 + 12x) = -8(x + 4) Reorder the terms: -12 + 12x = -8(4 + x) -12 + 12x = (4 * -8 + x * -8) -12 + 12x = (-32 + -8x) Solving -12 + 12x = -32 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -12 + 12x + 8x = -32 + -8x + 8x Combine like terms: 12x + 8x = 20x -12 + 20x = -32 + -8x + 8x Combine like terms: -8x + 8x = 0 -12 + 20x = -32 + 0 -12 + 20x = -32 Add '12' to each side of the equation. -12 + 12 + 20x = -32 + 12 Combine like terms: -12 + 12 = 0 0 + 20x = -32 + 12 20x = -32 + 12 Combine like terms: -32 + 12 = -20 20x = -20 Divide each side by '20'. x = -1 Simplifying x = -1
| 3x-9=3(x-4) | | 4xsquared-3x+1=0 | | 4.1y=8.2 | | 2/3x-1/7=4/5 | | 2/3m-1/7=4/5 | | 4y-2=2y+4 | | 2c-14=4c | | a(5x-6)=-45x+54 | | -9x-12x=84 | | .20x+.82=-.13x+3.34 | | 7+3(x+2)=4(x-7) | | -6b=-36 | | 7x-13+5x=2x-11 | | .2x+.82=-.13x+3.34 | | (36/(x+3))-(15(x+9))=1 | | (8/x)-1=8/(x-1) | | 36-91d-78-5d+3+6d= | | 9+m=26 | | n/12=10 | | sqrt(x-2)=9 | | .06/12= | | x=-5x^2-2x+16 | | 2r+2=5x-11 | | Abs(5x-1)-1=6 | | sqrt(x^2+9)-3=2 | | m+5m-8m+2= | | 4b-5b=5 | | 3(c+2)=24 | | m-5m-4m-5= | | 5s-7+4-2s+7z= | | x^4-18x^2+45=0 | | 39k+12=2k-11 |